Effect of Carbon Nanotubes on Mechanical Properties of Honeycomb - Shifa, M.; Tariq, F.; Baloch, R.A. (The Nucleus, 2017)
The present research paper discusses the effects of addition of carbon nanotubes on mechanical properties of hybrid honeycomb sandwich structure for high-tech applications. Hybrid honeycomb sandwich structure consists of aluminum honeycomb core sandwiched between multiscale (MWCNTs/CF) reinforced epoxy composite facing. Multiscale facing was fabricated through hand layup method followed by compression molding and curing. The sandwich panels were prepared through vacuum bagging technique and cured in oven. Three point bend test and compression test were performed to evaluate the mechanical performance of sandwich panels. Flat-wise tensile test was performed to assess the bonding strength between core and facing. Quasi-static indentation test was conducted to assess the ability of sandwich panel against low velocity impact. Neat honeycomb sandwich panel was also prepared via similar process but without MWCNTs addition for reference. A comparative study has been made between both sandwich materials. Results depict that compressive strength and flexural stiffness has been improved by 21% and 28% respectively by the addition of 0.2% MWCNTs in comparison to neat sandwich panel. Energy absorption capability of CNT-filled sandwich panel was also enhanced by 10% with reference to neat sandwich panel.